The Fate of Prosperity Gospel in Kenya - Alwala, Bernard (East African Journal of Traditions, Culture and Religion, 2020)
The prosperity gospel Pentecostalism is relatively new on the religious landscape which is swiftly expanding at breath-taking speed and now is a force to be reckoned with in Kenya. It has a greater chance of outliving the 21st century in view of the fact that it is widely and readily being accepted by all classes of people for its claim of physical and spiritual empowerment. The methodology adopted for this study was a phenomenological approach. The study uncovered that there are so many in favour of the expansion and consolidation of the prosperity gospel in Kenya. The paper affirmed the point that prosperity gospel in its entirety is not bad but what is needed is a change in the right focus of prosperity message. Even though there are aspects of negativism in prosperity preaching, the paper believes and concludes that God will eventually change the focus of prosperity message as preached by prosperity preachers to something more positive and rewarding for it to continue being relevant in Kenya.
free
Keywords: Fate; Gospel; Kenya; Neo-Pentecostalism; Prosperity